EVALUASI STANDAR HYGIENE SANITASI RUMAH POTONG HEWAN KM 5,5 BALIKPAPAN - Maslina, Maslina; Zulfikar, Iwan; Rahmawati Hamzah, Sri (Program Studi Kesehatan dan Keselamatan Kerja, 2022)
The high public demand for beef causes the intensity of slaughter to also increase. This causes attention to be focused on the existence of a slaughterhouse (RPH) as a meat production unit. At the Slaughterhouse (RPH) there are several people who are responsible for slaughtering animals, including those in charge of slaughtering cattle, namely the Halal Slaughterer and workers under the association. The job of a Halal Slaughterer is full of risks because accidents that often occur at RPH are industrial accidents, namely accidents that often occur in the workplace due to a source of danger. Departing from this background, the researchers conducted a study with the aim of evaluating the application of sanitary hygiene standards at the KM 5.5 Balikpapan Slaughterhouse so that they can produce ASUH (Safe, Healthy, Whole, and Halal) meat which refers to the SNI–01–6159–1999 standard. . The results of the research show that the Balikpapan City Slaughterhouse (RPH) has not complied with the standard requirements of SNI – 01 – 6159 – 1999. There are still many facilities such as public toilets and lack of lighting. There are no special facilities or places for washing work equipment and soap to clean equipment. There are still workers who have not worn PPE in the form of boots to prevent work accidents. There is no training or socialization regarding K3 or Hygiene at the Balikpapan Slaughterhouse